Pemanfaatan Media Edukatif Game Clash of Champions dalam Meningkatkan Minat Belajar Pembelajaran Matematika Sekolah Dasar - Risa Taviya Putri; Slamet Slamet; Fals Aldino (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to assess the effectiveness of Ruangguru's Clash of Champions (COC) game as an interactive learning tool, focusing on "fastest addition" to increase elementary school students' interest in mathematics. The basis of this study is the low interest and active participation of elementary school students in mathematics, especially in simple topics such as addition, which are often considered boring and uninspiring. By incorporating competitive game elements, time challenges, and immediate responses through COC, it is expected that students will be more enthusiastic, active, and interested in practicing addition at a faster pace. This study applies a descriptive qualitative method to explain in detail the phenomenon of utilizing educational media in the form of the game clash of champions (COC) to increase interest in learning mathematics in 3rd grade elementary school students. The results show that the time-based competition and leaderboard elements in COC are the main triggers for increased learning interest. The impact of this study indicates that competitive game media such as COC can be used as an alternative learning strategy for basic mathematics in elementary school, to increase student motivation and engagement.